Analysis of medico legal deaths in adolescence: An Autopsy based study at coaching city, Kota - Verma, Lalchandra; Kumar Garg, Vinod; Kumar Meena , Sachin (Journal of Indian Academy of Forensic Medicine, 2021)
An adolescent is defined as an individual aged between 11-19 years. They constitute about 1.2 billion worldwide, and about 21% of  Indian population. Mortality and morbidity occurring in this age group are mostly due to preventable causes. Mortalities in  adolescents are cause of concern because they are the future of nation forming a major demographic and economic force. The purpose  of this study is to analysis mortality in adolescents. Out of 1056 autopsies 94 victims were adolescents contributing 8.9% of total  autopsies. Male deaths were more (about 60%) than female (about 40%) and all deaths increased with an increase in age. More than  half of the total deaths (51%) were due to accidents, followed by suicides (43%). Females were prone to commit suicides. In suicidal  deaths the most common cause was hanging following by poisoning. Use of appropriate safety measures and strict law enforcement  may significantly reduce accidental deaths in adolescents. Suicides and homicides may be prevented by identification of risk factors,  significant family support and proper psychological counselling.
Keywords: Adolescent mortalities; Accidental deaths; Suicidal deaths